2014
DOI: 10.1080/10420150.2014.939176
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on the effects of Co-60 gamma radiation on polypropylene and polyimide

Abstract: Polypropylene (PP) and polyimide (PI), which belong to entirely different classes of polymers, are irradiated by Co-60 gamma radiation under similar doses and similar conditions in the dose range varying from 57.6 to 230.4 kGy. The radiation responses of these two polymers are analyzed by various characterizations such as Fourier transform infrared, UV-visible, energy-dispersive spectroscopy, X-ray diffraction, scanning electron microscopy and contact angle. PP shows substantial modifications in its structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…A comparison of Figure (A) with Figure (C) reveals the smooth and compact surface of the PPP particles, which developed pores, globules, and blisters of various sizes after aging. The creation of porosity and the rough surface was caused by the reaction of radiation and thermally initiated free radicals in PPP with oxygen . The increased oxygen content in PPw also confirmed the occurrence of oxidation in PPw.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…A comparison of Figure (A) with Figure (C) reveals the smooth and compact surface of the PPP particles, which developed pores, globules, and blisters of various sizes after aging. The creation of porosity and the rough surface was caused by the reaction of radiation and thermally initiated free radicals in PPP with oxygen . The increased oxygen content in PPw also confirmed the occurrence of oxidation in PPw.…”
Section: Resultsmentioning
confidence: 65%
“…The intensity and shape of the aforementioned crystalline zone peaks indicated that the X c of PPw was not significantly affected and was found to be 39.91%. The mobility of radiation‐induced free radicals was affected because of the slight change in X c . However, after radiation grafting, the reduction in the height of the crystalline peaks in diffractogram C took place despite the fact there was no change in Bragg's angle.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristic strong peaks between 3000 and 2800 cm −1 indicate the asymmetric CH stretching vibrations and the symmetric CH stretching vibrations in CH 3 , CH 2 , and CH groups for the pure PP [see Figure (b)] . The strong peak at 1455 and 1376 cm −1 also indicated the asymmetric and the symmetric scissoring vibrations of the methyl group (CH 3 ), respectively .…”
Section: Resultsmentioning
confidence: 99%
“…PI and materials based on it have a high radiation resistance to gamma radiation. It was revealed that irradiation of PI by a 60 Co source up to a dose of 230.4 kGy (the maximum accumulated dose in the work) does not cause significant changes in the structure and properties of PI, which were characterized by Fourier transform infrared spectroscopy, energy dispersive spectroscopy, X-ray phase analysis and scanning electron microscopy (Mathakari et al, 2014). PI demonstrated remarkable stability for the properties under study.…”
Section: Radiation Resistance Of Pi/wo 2 Compositementioning
confidence: 96%